Pengaruh TAT0, Firm Size, ROE dan NPM Terhadap Pertumbuhan Laba Pada Sektor Industri 2020–2024 - Berliani Putri, Nabila; Maya Hapsari, Ira; Waskito, Jaka (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
This study aims to examine the effect of Total Assets Turnover (TATO), Firm Size, Return On Equity (ROE), and Net Profit Margin (NPM) on Profit Growth in industrial sector companies on the Indonesia Stock Exchange (IDX) for the period 2020-2024. Using secondary data from annual financial reports with a sample off 100 observations from 67 companies after purposive sampling. The analysis methods includes descriptive statistics, classical assumption tests, and multiple linear regression through SPSS 27. Where the results of the study show that ROE has a significant positive effect on profit growth, while TATO, Firm Size, and NPM are not significant, although all four variables simultaneously have a significant impact. These findings indicate ROE as a key factor in increasing profitability that emphasizes the importance of equity management, while asset efficiency TATO and NPM have a smaller effect, thus providing practical implications for management and investors that optimizing shareholder equity has a greater impact than focusing on operational efficiency or margin expansion, while contributing to the corporate finance literature by identifying determinants of financial performance specific to industries in emerging markets.